A simple use of camera traps for photogrammetric estimation of wild animal traits. (27th May 2020) - Cui, S.; Chen, D.; Sun, J.; Chu, H.; Li, C.; Jiang, Z.
Abstract: The measurement of physical traits of animals is an important topic in animal ecology and wildlife management, but it is quite difficult to achieve an acceptable level of accuracy, especially for free‐ranging wild animals. As a non‐invasive method, camera trapping has become a common tool for detecting and monitoring wild animals. In this study, we combined camera‐trapping images and a photogrammetry technique to present a camera trap‐based photogrammetric estimation (CTPE) approach for robust measurement of morphological traits of animals. We first tested our method in a captive population of fallow deer ( Dama dama ) and compared the estimated shoulder heights by CTPE with corresponding hand measurements. The results revealed a remarkable accuracy, with an expected measurement error within ± 5 cm. Second, we mainly demonstrated a field application of CTPE in a wild population of Altai wapiti ( Cervus elaphus sibiricus ) in the Kanas National Nature Reserve, Xinjiang, China. For wapiti, we found that the average shoulder height of males was 135 ± 9 cm (mean ± sd, n  = 30) and that of females was 125 ± 6 cm (n = 37), with all data significantly fitting a normal distribution. We did not find any differences in CTPE results among cameras, between photograph types (colour vs. black and white) or temperatures. No significant difference existed between our results and the hand‐measured shoulder heights of wapiti from deer farms. Finally, we discussed the strengths, limitations and potential extensions of the method. We suggest that the combination of camera trapping and the photogrammetry technique is quite promising and that CTPE has great potential in wildlife field investigations. Abstract : The measurement of morphological traits is important for animal ecology, but it is quite difficult to achieve an acceptable level of accuracy for free‐ranging animals. Here we combined camera‐trapping images and a photogrammetry technique to test a camera trap‐based photogrammetric estimation (CTPE) for robust measurement of shoulder heights of animals. The results indicate that CTPE is practical and valid. We suggest that CTPE would be a promising tool for future field‐based research.